DEVELOPMENT AND MANAGEMENT OF INDUSTRY-SPECIFIC SCIENTIFIC PROJECTS IN THE FIELD OF ORGANIC PRODUCTION - SKOROKHOD, Iryna; PAVLOV, Kostiantyn; PAVLOVA, Olena; SYCHUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of the development of organic production has been actively discussed in recent decades, and this is facilitated by the grave concern of some people about the future of the environment and human health. Despite the world’s population increase, the predicted food crisis, according to some scientific studies, has not yet become widespread. Agricultural production is skyrocketing, and its differentiation is taking place due to economic needs, which allows us to postpone the probable food collapse further. Due to the increase in demand for organic products both in the global and domestic markets, there is a need to develop effective technologies for growing organic crops. Therefore, studying the world experience of scientific and educational support for developing the organic production sector is necessary. This study aims to assess the management of industry-specific scientific projects in the field of organic production in Ukraine. This paper carefully analyzes the current state of the organic sector in Ukraine, identifies the main challenges and opportunities, and proposes specific strategies for increasing production volumes and successfully entering international markets. The importance of cooperation between government agencies, businesses, and the public for achieving success in this area is emphasized. This empirical work examines how the armed conflict affects the organic sector of Ukraine, focusing on increasing risks for this sector. The dynamics of changes in agricultural land designated for organic production were studied, and the reasons for the reduction in the number of operators in the organic market were analyzed in detail. The leading companies in the market, based on the number of certified producers of organic agricultural products, were identified. Factors leading to decreased product sales on the domestic market were identified. A SWOT analysis of the effectiveness of organic production in Ukraine under martial law was conducted. An analysis of international standards and requirements that can improve the competitive position of Ukrainian producers at the global level was also conducted. The study used reports and materials from the International Federation of Organic Agriculture Movements (IFOAM) and documents from Organic Standard LLC and Organic Ukraine NGO. In addition, various online sources were used, and the status of international cooperation projects aimed at developing the organic market was analyzed. Given the rapid growth in demand for organic products, the results of this study can become a valuable resource for agricultural enterprises, government organizations, research institutions, and international partners interested in cooperating with Ukrainian organic producers. Analysis and coverage of the review of the development of organic culture in leading industry scientific projects made it possible to form new directions for improving the introduction of organic agricultural production at all levels of preparation, which will contribute to improving the potential of the organic sector both within agricultural reorganization programs of this industry and beyond in cooperation with other countries.